Enhancing resilience towards summer storms from a spatial planning perspective. Lessons learned from summer storm Ela. - Schmitt, Hanna Christine; Greiving, Stefan (Springer, 2018)
Der Text erläutert die Stärken und Grenzen der Raumplanung im Umgang mit allgegenwärtigen und nicht voraussagbaren extremen Wetterereignissen am Beispiel des Sommersturms Ela, der im Juni 2014 große Teile Westdeutschlands verwüstete.

Every year, convective extreme weather events like summer storms, hail and heavy precipitation cause enormous damages to assets, values and human lives, especially in urban areas. Although highly relevant for the field and expertise of spatial planning, so far those events are addressed rather poorly, if at all. This is mainly for two reasons: for one, convective extreme events are of ubiquitous character, meaning they have unknown probability and place of occurrence, i.e. are accompanied by great uncertainties. For another, spatial planning does not dispose of convenient concepts and instruments to address events with an intangible hazard component, as they are spatially not describable and therefore risk analyses presumably inapplicable. Ultimately, ubiquitous extreme weather events challenge urban disaster resilience and call for enhanced risk management approaches. This chapter discusses the strengths and limitations of spatial planning in dealing with ubiquitous extreme weather events, using the example of summer storm Ela, which devastated large parts of Western Germany in June 2014.
Keywords: Raumplanung; Stärken-Schwächen-Analyse; Risikomanagement; Naturkatastrophe; Sturm; Orkan